Dampak Rasio Kecukupan Modal dan Risiko terhadap Profitabilitas pada Bank Konvensional di Indonesia - Nurul Kamila; Febrisi Dwita; Triyogo Moelyo Adhi; Nia Desliana (Studi Ilmu Manajemen dan Organisasi, 2024)
Purpose: To determine the effect of capital adequacy ratio, market risk, credit risk, liquidity risk, operational risk, bank size, and other variables on banking profitability in Indonesia. Methodology: Panel data regression analysis; purposive sampling; capital adequacy ratio, market risk, credit risk, liquidity risk, operational risk, bank size as instruments; 39 banks listed on Indonesia Stock Exchange; return on assets as dependent variable.Results: Capital adequacy ratio and bank size have a positive and significant influence on profitability. Credit risk and operational risk have a significant negative effect. Market risk and liquidity risk have no significant effect.Conclusions: when the risk of credit default increases, banks experience a decrease in income generated from lending activities. Thus, effective credit risk management is essential for banks to minimize the risk of default and maintain profitability stability. The higher the operational risk, the lower the bank's profitability level.Limitations: The study is limited to data from banks listed on the Indonesia Stock Exchange between 2018-2024, so it may not reflect conditions outside this period or region.Contribution: This research is useful in the fields of banking management, corporate finance, and investment strategy.